If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 8 + -1y = y + 4 Reorder the terms: 8 + 3y + -1y = y + 4 Combine like terms: 3y + -1y = 2y 8 + 2y = y + 4 Reorder the terms: 8 + 2y = 4 + y Solving 8 + 2y = 4 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 8 + 2y + -1y = 4 + y + -1y Combine like terms: 2y + -1y = 1y 8 + 1y = 4 + y + -1y Combine like terms: y + -1y = 0 8 + 1y = 4 + 0 8 + 1y = 4 Add '-8' to each side of the equation. 8 + -8 + 1y = 4 + -8 Combine like terms: 8 + -8 = 0 0 + 1y = 4 + -8 1y = 4 + -8 Combine like terms: 4 + -8 = -4 1y = -4 Divide each side by '1'. y = -4 Simplifying y = -4
| 4k^2-2k-5=0 | | 3x+19=7x-11 | | 4x-5(x-2)=9c-14 | | 4(n-8)+5(-6-2n)=-68 | | 4(n-8)+5(-6-2n)=-69 | | 3x+7=5x-x+0 | | 29=a+7 | | v=15x^3+52x^2+32x | | -12t-28=9t+47-(-4t) | | 3v+4=19 | | x^2+20x+42=0 | | 2x+72=12-3x | | 0.8+0.25x=0 | | 9(x-6)=6-30 | | 4q+-24=12 | | x+9f+10=5j | | 15(3x+1)-243(5x-2)=0 | | 25/x+6=5/6 | | 1n-1=18 | | -9x+7y=2 | | -19w+-20=18 | | c-2y=24 | | -13x+6=-12-9 | | x-2-(3+(7-2x))=-6 | | 0.625x(a-2)=10 | | 5x+2=8x+11 | | x+7+2x+3-40=0 | | 4(4x+25)-3(4x-1)=5(4x-7) | | 2x-(5-(3x+4))=x-5 | | (5c-4c)+(c-3c)= | | 5(12-3x)+x=3(-2x+4) | | x=(x+1)*0.62 |